2020
DOI: 10.1093/jisesa/ieaa136
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Approach for Detecting Stage-Specific Predation onLygus hesperus(Hemiptera: Miridae)

Abstract: A molecular gut analysis technique is described to identify predators of Lygus hesperus (Knight), a significant pest of many crops. The technique is unique because it can pinpoint which life stage of the pest was consumed. Sentinel egg masses designed to mimic the endophytic egg-laying behavior of L. hesperus were marked with rabbit serum, while third instar and adult L. hesperus were marked with chicken and rat sera, respectively. Then, the variously labeled L. hesperus life stages were introduced into field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Presumably, L. rugulipennis nymphs use pollen and nectar of chrysanthemum flowers which might be food sources of higher quality than leaves for nymphal survival, although we found no differences in terms of development time. Besides plant quality, also cannibalism among nymphs might have determined the number of nymphs developing to the adult stage since cannibalism has been observed by Hagler et al (2020) for L. hesperus at low levels. Although L. rugulipennis develops better on chrysanthemum plants at the flowering stage, they are also able to reproduce successfully on small, vegetative chrysanthemum plants without any additional food source.…”
Section: Discussionmentioning
confidence: 98%
“…Presumably, L. rugulipennis nymphs use pollen and nectar of chrysanthemum flowers which might be food sources of higher quality than leaves for nymphal survival, although we found no differences in terms of development time. Besides plant quality, also cannibalism among nymphs might have determined the number of nymphs developing to the adult stage since cannibalism has been observed by Hagler et al (2020) for L. hesperus at low levels. Although L. rugulipennis develops better on chrysanthemum plants at the flowering stage, they are also able to reproduce successfully on small, vegetative chrysanthemum plants without any additional food source.…”
Section: Discussionmentioning
confidence: 98%
“…(Hemiptera), Neuroptera, Formicidae (Hymenoptera) and Araneae (Bolda et al., 2019; Hagler, 2011). The categories represent functional groups identified by previous lygus bug predation studies (Hagler et al., 2020; Hagler et al., 2020; Leigh & Gonzalez, 1976; Perkins & Watson, 1972; Wilson & Gutierrez, 1980; Zink & Rosenheim, 2008). The lygus bug complex in this region primarily consists of Lygus hesperus , and also includes small proportions of L. elisus and L. lineolaris (Hagler, Nieto, et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Molecular tools are also useful for the study of predator-prey interactions between Lygus species and their consumers. Hagler et al [ 206 ] reported a molecular gut analysis technique called universal food immunomarking technique (UFIT) for tagging L. hesperus nymphs and adult stages using a protein marker. This UFIT technique combined with enzyme-linked immunosorbent assays (ELISA) identified the different stage-specific predators of Lygus species, and this information could contribute to IPM strategies against this pest.…”
Section: Integrated Management Strategiesmentioning
confidence: 99%